2021
DOI: 10.3390/nano11030798
|View full text |Cite
|
Sign up to set email alerts
|

New Sustainable, Scalable and One-Step Synthesis of Iron Oxide Nanoparticles by Ion Exchange Process

Abstract: This work introduces an innovative, sustainable, and scalable synthesis of iron oxides nanoparticles (NPs) in aqueous suspension. The method, based on ion exchange process, consists of a one-step procedure, time and energy saving, operating in water and at room temperature, by cheap and renewable reagents. The influence of both oxidation state of the initial reagent and reaction atmosphere is considered. Three kinds of iron nanostructured compounds are obtained (2-lines ferrihydrite; layered-structure iron oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…The microscopic investigations showed that the ferrihydrite formed aggregates made of poorly ordered ferrihydrite nanoparticles (ca. 5 nm in size), results that are in accordance with other literature findings [ 41 , 43 , 46 , 47 , 48 , 49 ].…”
Section: Discussionsupporting
confidence: 93%
“…The microscopic investigations showed that the ferrihydrite formed aggregates made of poorly ordered ferrihydrite nanoparticles (ca. 5 nm in size), results that are in accordance with other literature findings [ 41 , 43 , 46 , 47 , 48 , 49 ].…”
Section: Discussionsupporting
confidence: 93%
“…In fact, interpolating the experimental data provided the fundamental information that the simonkolleite logarithmic decrease (R 2 = 0.9883) was directly related to the symmetric ZnO increase (R 2 = 0.9883), according to the following equations: These results, together with CC values reported in Table 1, are evidence of the novelty and originality of this synthesis, reported for the first time here. In principle, we expected that the fast decrease in chlorides, which occurred at the beginning of the exchange reaction, corresponded to their absorption on the surface of the anionic exchange resin [44,[49][50][51][52], as described by the following formula:…”
Section: Resultsmentioning
confidence: 99%
“…After 90 min, we stopped the reaction and separated the resin from the produced aqueous suspension using a metallic sieve (180 µm aperture). Next, we placed the exhausted resin in a column, and an 8% wt NaOH aqueous solution was applied at a flow rate of approximately 1 L/min until the resin was completely regenerated and ready for use in a new synthesis cycle [44].…”
Section: Zno Nanoparticles Synthesismentioning
confidence: 99%
“…Due to the water viscosity and the high ionic strength, hydrolysis reactions are favored without any catalyst. Traditionally, this effect is more pronounced closer to the critical point of water (374 • C and 22.1 MPa) [85][86][87].…”
Section: Hydrothermal Synthesismentioning
confidence: 99%